ANALISIS PENGARUH KINERJA KEUANGAN DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI (STUDI PADA PEMERINTAH KOTA MEDAN) - Ernawati, Yusrida (CV. Lafadz Jaya, 2024)
The aim of the research carried out is to find out whether there is an influence between financial performance as measured through fiscal independence, regional financial effectiveness and efficiency on economic growth. The research carried out also attempts to prove whether there is an influence of capital expenditure on economic growth. As for economic growth, it is also measured using a GDP growth ratio. This research is descriptive and quantitative research where the data that has been used is secondary data obtained from the Medan City APBD for the last 10 years, namely from 2014 to 2023. Analysis of the data used in this research uses an analysis of multiple linear regression. The research results inform that in the last 10 years (2014-2023) Fiscal Independence and Financial Effectiveness have had a significant influence on Economic Growth and Financial Efficiency has had a significant influence on economic growth in Medan City. Furthermore, capital expenditure also influences the economic growth of Medan City.